Potret Pembelajaran Dan Implementasi Kaidah Fikih: Kitab al- Madkhal Ila al-Qawa’id al-Fiqhiyyah dan Buku Simpel dan Mudah Menguasai 175 Kaidah Fikih di Ma’had Aly Situbondo - M Soleh Shofier (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
This research will photograph the learning and implementation of fiqh rules at Ma'had Aly Situbondo. There are several basic reasons why this research was conducted. Among other things, Ma'had Aly Situbondo has an important role in grounding the principles of jurisprudence which are intertwined with the study of jurisprudence and jurisprudential suggestions, which unfortunately has escaped the attention of many researchers. Apart from that, Ma'had Aly Situbondo has his own patterns and characteristics in designing learning and implementing fiqh rules. This research includes descriptive research with a qualitative approach. The data collection technique was interviews and observations of Ma'had Aly's documents including the Buku al-Madkhal Ila al-Qawaid al-Fiqhiyyah and the Simple and Easy to Master Book of 175 Rules of Jurisprudence. In conclusion, there are four models that characterize Ma'had Aly Situbondo in studying the rules of jurisprudence. First, the step of reading the rules of jurisprudence simultaneously when entering lectures is around 5-7 minutes, which must be read aloud, looking and listening using the book Simple and Easy to Master 175 Rules of Jurisprudence. Second, read the text of the book al-Madkhal Ila al-Qawaid al-Fiqhiyyah to discuss it. Third, memorize and deposit. Fourth, write a paper that discusses jurisprudential legal issues using a jurisprudential approach. In a more dynamic way, the implementation of Islamic jurisprudence principles is also actualized through the writing of popular and scientific articles. The actualization space is the Tanwirul Afkar Magazine which is based on print while the online one is the website maalysitubondo.ac.id. Apart from being a reinforcement in scientific studies, the rules of fiqh also become reflections in the daily activities of students and are made into short stories that include the rules of fiqh.